Community Policing and Police Agency Accreditation in the United States, 1992 and 1994 - Cordner, Gary W. ([Verlag nicht ermittelbar], 1999)
This study was undertaken to examine the compatibility of law enforcement agency accreditation and community policing. It sought to answer the following questions: (1) Are accreditation and community policing compatible? (2) Do accreditation and community policing conflict? (3) Does accreditation support community policing? (4) Did any of this change with the 1994 "top-down" revision of the Commission on Accreditation for Law Enforcement Agencies (CALEA) standards? To that end, the researchers conducted separate content analyses of the 897 accreditation standards of the Commission on Accreditation for Law Enforcement Agencies (CALEA) in effect at the end of 1992 and the revised set of 436 standards published in 1994. The standards were coded on 27 variables derived from the literature on community policing and police administration. Information was collected on the basics of each accreditation standard, its references to issues of community-oriented policing (COP) and problem-oriented policing (POP), and general information on its compatibility, or conflict with COP and POP. Basic variables cover standard, chapter, section, and applicability. Variables focusing on the compatibility of community-oriented policing and the accreditation standards include sources of legitimacy/authorization, community input, community reciprocity, geographic responsibility, and broadening of functions. Variables on problem-oriented policing include level of analysis, empirical analysis, collaboration with nonpolice agencies, evaluation/assessment, and nature of the problem. Variables on management and administration concern officer discretion, specialization by unit, specialization by task, formalization, centralization, levels/hierarchy, employee notification, employee involvement, employee rights, specific accountability, and customer orientation. General information on the compatibility or conflict between a standard and community-oriented policing/problem-oriented policing includes overall restrictiveness of the standard, primary strategic affiliation, focus on process, and focus on administration.